2004
DOI: 10.1111/j.1365-246x.2004.02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal evolution of induced seismicity at Açu reservoir, NE Brazil

Abstract: S U M M A R YWe present the spatio-temporal evolution of seismicity recorded by eight three-component digital seismographs in operation continuously during a 3 yr period (1994 August to 1997 at Açu reservoir, NE Brazil. The Açu dam is a 34 m high earth-filled dam constructed in 1983 May on an area of Precambrian shield. Based on seismic monitoring between 1987 and 1989 using single-component analogue seismographs, previous workers concluded that the seismic activity was a case of reservoir-induced seismicity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 25 publications
(43 reference statements)
4
60
0
1
Order By: Relevance
“…Namely, the increase of seismic activity is related to the complex impact of the water lake on the earth crust under the reservoir and is explained by the changes in ambient stress conditions due to the load (unload) of the water or, respectively, to the increase of interstitial pore pressure in the rock matrix beneath the reservoir due to downward percolation of fluid. It is also known that the water reservoir related changes in the seismicity of surrounding area -RIS, decreases after several years down to the level when even lesser earthquakes may occur with lower magnitudes compared to the basic level of the local seismic activity [1,15]. At the same time, the underlying dynamics of the mentioned decrease of seismic energy release, following the initial RIS activity is still an open problem.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Namely, the increase of seismic activity is related to the complex impact of the water lake on the earth crust under the reservoir and is explained by the changes in ambient stress conditions due to the load (unload) of the water or, respectively, to the increase of interstitial pore pressure in the rock matrix beneath the reservoir due to downward percolation of fluid. It is also known that the water reservoir related changes in the seismicity of surrounding area -RIS, decreases after several years down to the level when even lesser earthquakes may occur with lower magnitudes compared to the basic level of the local seismic activity [1,15]. At the same time, the underlying dynamics of the mentioned decrease of seismic energy release, following the initial RIS activity is still an open problem.…”
Section: Introductionmentioning
confidence: 96%
“…Generally, the scientific and practical importance of investigation of possible mechanisms related to the dynamics of influence of high dam water reservoirs on local earthquakes generation is well acknowledged [1,15,22,23,25,26]. Since the mid of the past century, the RIS has been observed at many reservoirs and their geological, hydrological, and physical features remain subjects of intense investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of reservoir-triggered seismicity (RTS) has been associated with a number of potential factors including the rate of loading, highest water level reached and the duration of retention of high water levels (Kaiser 1953;Gupta et al 1972a, b). Other studies have investigated the role of reservoir loading (e.g., Gough and Gough 1970a, b;Bell and Nur 1978;Roeloffs 1988) and the influence of pore fluid pressure (Snow 1972;Talwani et al 1999;Do Nascimento et al 2004). While major advancements have been made towards elucidating the role of individual parameters in triggering earthquakes, an integrated model that explains the genesis of RTS is unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Devi et al (2008) of the Gilgel-Gibe reservoir predicted that if no action is taken, it would be silted up within 24 years. They estimated the total amount of sediment deposited in the reservoir at 4.50 × 10 7 tons/year.…”
Section: Sustainability Of Dams and Reservoirsmentioning
confidence: 98%
“…Eutrophication was demonstrated by Devi et al (2008) in the Gilgel-Gibe reservoir (south-western Ethiopia) by the presence of water pollution, particularly increased nitrogen and phosphorus concentrations. The authors concluded that pollution in that man-made lake was apparently due to fertilizers, decomposition of organic waste (erosion and (or) sedimentation), and detergents in waste water emitted in upstream towns.…”
Section: Eutrophicationmentioning
confidence: 99%